Seidel Laplacian and Seidel Signless Laplacian energies of commuting graph for dihedral groups - Romdhini, Mamika Ujianita; Nawawi, Athirah; Syechah, Bulqis Nebula; Al-Quran, Ashraf (Penerbit UTM Press, 2024)
In this paper, we discuss the energy of the commuting graph. The vertex set of the graph is dihedral groups and the edges between two distinct vertices represent the commutativity of the group elements. The spectrum of the graph is associated with the Seidel Laplacian and Seidel signless Laplacian matrices. The results are similar to the well-known fact that the energies are not odd integers. We also highlight the relation that the Seidel signless Laplacian energy is never less than Seidel Laplacian energy. Ultimately, we classify the graphs according to the energy value as the hyperenergetic.